Tetratricopeptide repeat domain 9A negatively regulates estrogen receptor alpha activity - Shrestha, Smeeta (2015)
Tetratricopeptide repeat domain 9A (TTC9A) is a target gene of estrogen and progesterone. It is over-expressed in breast cancer. However, little is known about the physiological function of TTC9A. The objectives of this study were to establish a Ttc9a knockout mouse model and to study the consequence of Ttc9a gene inactivation. The Ttc9a targeting vector was generated by replacing the Ttc9a exon 1 with a neomycin cassette. The mice homozygous for Ttc9a exon 1 deletion appear to grow normally and are fertile. However, further characterization of the female mice revealed that Ttc9a deficiency is associated with greater body weight, bigger thymus and better mammary development in post-pubertal mice. Furthermore, Ttc9a deficient mammary gland was more responsive to estrogen treatment with greater mammary ductal lengthening, ductal branching and estrogen target gene induction. Since Ttc9a is induced by estrogen in estrogen target tissues, these results suggest that Ttc9a is a negative regulator of estrogen function through a negative feedback mechanism. This is supported by in vitro evidence that TTC9A over-expression attenuated ERα activity in MCF-7 cells. Although TTC9A does not bind to ERα or its chaperone protein Hsp90 directly, TTC9A strongly interacts with FKBP38 and FKBP51, both of which interact with ERα and Hsp90 and modulate ERα activity. It is plausible therefore that TTC9A negatively regulates ERα activity through interacting with co-chaperone proteins such as FKBP38 and FKBP51.